Otentisitas Khithbah dan Pemberian Cincin Pinangan di Aceh - Munawir, Munawir (Al-Mizan, 2023)
The engagement before marriage, has the authenticity of the rules that apply in society because it is inseparable from the influence and role of Islamic law and customs that apply in society, so it is very appropriate if we look at the historical background of the engagement engagement and giving of engagement rings for research in the marriage cluster still needs to be done to increase the intellectual treasury in understanding the realm of the implementation of a proposal that takes place in society against the problematic implementation of the provisions of the proposal that apply in the provisions of Islam in the community of Gampong Buket Teukueh, the researcher wants to study with the formulation of the problem of the authenticity of the proposal that is permitted in Islamic law and the practice of proposals and giving engagement rings in Gampong Buket Teukueh. The purpose of the study is to determine the authenticity of the proposal that is permitted in Islamic law and the practice of proposals and giving engagement rings in Gampong Buket Teukueh. The research method used by the author in this study is qualitative with the type of field research in Gampong Buket Teukueh, the data source is an interview with the apparatus and the community of Gampong Buket Teukueh with a descriptive analysis method. The results of the study are that the law of proposals in the provisions of sharia is that proposals (khitbah) are allowed to be held. This authenticity is as stated in the Al-Quran, Surah Al-Baqarah, verse 235 and the practices carried out by the community regarding the proposal process in Gampong Buket Teukueh as in sharia, including the family of the suitor and involving the Imum Gampong of both families during the proposal process and witnessed by both parties from the families of the suitor and the proposed party.